Implementasi Ajaran Islam Di Tengah Agama-Agama Di Indonesia - Mahfud Mahfud (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2020)
The concept of religion and faith. Logical argumentation buildings are always built as an effort to claim the truth of each religion. In the history of mankind, it is not uncommon for wars to be used as a way to explain one concept of truth from each religion. In fact, Islam as a revealed religion is a product of heaven when it comes into contact with humans who have worldly human attitudes and must be able to capture the message of heaven that is so holy. Religious teachings are considered as something holy, so it is not uncommon for everyone who embraces them to place religion and religious teachings in a high (sacred) place. Religious teachings are sourced from holy books whose holiness is of great value not only in form but in language and meaning. From that, many of the adherents of religion do not come to an understanding of the unity of the concept in religious life so that the attitude of blaming and accusing others is worse than us, it often happens. Such a thing will undoubtedly lead to conflicts between religious adherents and this will trigger divisions among religious followers in the context of the Indonesian nation. Therefore, this paper is here as an effort to understand us about how to ground religion which is the commandment of the heavens.